Does highway project bundling policy affect bidding competition? Insights from a mixed ordinal logistic model. (March 2021) - Qiao, Yu; Labi, Samuel; Fricker, Jon D.
Abstract: Highway transportation project bundling can significantly reduce project delivery cost but could cause undesirable consequences such as reduced market competition. As such, bundling policy needs to be guided by a careful assessment of the potential impacts of bundling on bidding competition. This paper analyses the effect of project bundling policies on market competition using random-effects mixed ordinal logistic modelling, a probabilistic approach. The paper also investigates the variations of such effects across the different project types. The bundling policy factors that were found to be significantly impact bidding competition were the bundle size, bundling combination, and spatial proximity. The results suggest that bundled projects are generally associated with lower bidding competition compared to standalone projects, for all work categories except traffic projects. Further, where the bundled projects have proximal location, the bidding competition is generally higher. It was also determined that the different highway project types exhibit significant differences regarding the effect of bundling on competition: bundling policy (vis-à-vis standalone policy) generally leads to less intense competition for bridge, road, small-structures, miscellaneous, and utility projects, and more intense competition for traffic projects. In addition, it was found that there is a significant improvement on the model performance by including a random effects specification which diagnosed and addressed the unobserved heterogeneity that exists across the contract-letting years, for all the project types. The paper's models can help highway agencies not only estimate the expected number of bidders for a given project under different bundling policies but also assess the effects of the bundling policy-related factors on bidding competition.